Personality assessment usage and mental health among Chinese adolescents: A sequential mediation model of the Barnum effect and ego identity - Hua, Jie; Zhou, Yi-Xin (Frontiers in Psychology, 2023)
Introduction Adolescence is a crucial period for establishing ego identity and becoming a social individual. However, numerous adolescents suffer from mental health problems, especially after the conditions surrounding the COVID-19 outbreak. Personality assessments are often used when adolescents look for psychological self-help services. However, the meaning and mechanism of these personality assessments remain unknown. Taking the increasingly popular MBTI personality assessment as an entry point, the current study examined the potential sequential mediation relationship of Barnum effect – ego identity on the link between personality assessment usage and mental health. Methods The current study surveyed 308 Chinese high school students, including 109 males and 199 females. MBTI use, Barnum effect, ego-identity, and mental health (subjective well-being, depression, and anxiety) were measured by seven questionnaires, respectively. Sequential mediation models were constructed to analyze the relationship. Results The results indicate that the Barnum effect and ego identity together function as a sequential mediation path between personality assessment use and teenagers’ mental health, including subjective well-being, depression, and anxiety. Specifically, a higher level of MBTI use triggers a stronger Barnum effect. The Barnum effect then promotes adolescents’ ego identity, ultimately increasing subjective well-being levels and reducing anxiety and depression. Discussion Our findings suggest that by properly using personality assessment and stimulating the Barnum effect, we can enhance adolescents’ mental health. The theoretical and practical implications of our findings are discussed.